Cognitive State following Stroke: The Predominant Role of Preexisting White Matter Lesions - Efrat Kliper; Einor Ben Assayag; Ricardo Tarrasch; Moran Artzi; Amos D. Korczyn; Shani Shenhar‐Tsarfaty; Orna Aizenstein; Hen Hallevi; Anat Mike; Ludmila Shopin; Natan M. Bornstein; Dafna Ben Bashat (2014)
Background and purpose Stroke is a major cause of cognitive impairment and dementia in adults, however the role of the ischemic lesions themselves, on top of other risk factors known in the elderly, remains controversial. This study used structural equation modeling to determine the respective impact of the new ischemic lesions' volume, preexisting white matter lesions and white matter integrity on post stroke cognitive state. Methods Consecutive first ever mild to moderate stroke or transient ischemic attack patients recruited into the ongoing prospective TABASCO study underwent magnetic resonance imaging scans within seven days of stroke onset and were cognitively assessed one year after the event using a computerized neuropsychological battery. The volumes of both ischemic lesions and preexisting white matter lesions and the integrity of the normal appearing white matter tissue were measured and their contribution to cognitive state was assessed using structural equation modeling path analysis taking into account demographic parameters. Two models were hypothesized, differing by the role of ischemic lesions' volume. Results Structural equation modeling analysis of 142 patients confirmed the predominant role of white matter lesion volume (standardized path coefficient β = −0.231) and normal appearing white matter integrity (β = −0.176) on the global cognitive score, while ischemic lesions' volume showed no such effect (β = 0.038). The model excluding the ischemic lesion presented better fit to the data (comparative fit index 0.9 versus 0.092). Conclusions Mild to moderate stroke patients with preexisting white matter lesions are more vulnerable to cognitive impairment regardless of their new ischemic lesions. Thus, these patients can serve as a target group for studies on cognitive rehabilitation and neuro-protective therapies which may, in turn, slow their cognitive deterioration.